2015
DOI: 10.1016/j.jval.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Preferences for Bone Metastases Drug Therapy in the United States

Abstract: Physicians indicated that clinical attributes are important when considering bone-targeting therapy for bone metastases, but consistent with the current health care landscape, patient out-of-pocket cost was the most important. With health care costs being increasingly shifted to patients, physicians require accurate information about co-pays and assistance programs to avoid patients receiving less costly, yet potentially inferior, treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…efficient mode of bta administration is a desirable aspect of this attribute. Overall, the findings in the study appear to be consistent with results from similar preference-elicitation studies among physicians in the United States 33 and Europe 34,35 , for whom both efficacy and a reduced risk of renal impairment represented the primary goals in their decision-making process.…”
Section: Discussionsupporting
confidence: 83%
“…efficient mode of bta administration is a desirable aspect of this attribute. Overall, the findings in the study appear to be consistent with results from similar preference-elicitation studies among physicians in the United States 33 and Europe 34,35 , for whom both efficacy and a reduced risk of renal impairment represented the primary goals in their decision-making process.…”
Section: Discussionsupporting
confidence: 83%
“…This consistently greater compliance observed throughout the 3-year study period confirms and extends the 1-year findings reported by Hernandez et al As suggested previously, the better compliance among denosumab patients may reflect more convenient dosing and physicians’ motivation to sustain “on-time” dosing schedules in order to achieve the full therapeutic benefit demonstrated in the denosumab clinical trials. Recent research into physician preferences for bone metastasis drug therapy indicates that the most important considerations are delaying SREs and worsening of pain, while minimizing the risk of renal impairment [16, 23]. Renal toxicity is also an important factor when patients consider BTA therapy, and the known renal toxicity of IV BPs complicates treatment since renal function must be closely monitored in patients using zoledronic acid and doses may be delayed or skipped depending on the patient serum creatinine levels [16, 24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Although early applications were used to quantify process utility [9,10], more recent applications have focused on patient preferences for health status [11,12], screening [13], prevention [14,15], pharmaceutical treatment [16,17], therapeutic devices [18,19], diagnostic testing [20,21], and end-of-life care [22,23]. In addition, conjoint analysis methods have been used to study decision making among stakeholders other than patients, including clinicians [24][25][26], caregivers [25,27], and the general public [28,29].…”
Section: Introductionmentioning
confidence: 99%